Collaboration between Madrasah Ibtidaiyah and Diniyah: (Strengthening Religious Character, Science, and Technology) - Fina Kholij Zukhrufin; Faridi Faridi; Khozin Khozin (Yayasan Letiges Konsultan Sosial, 2024)
Education at Madrasah Ibtidaiyah and Madrasah Diniyah could be more optimal in maximizing students' religious, science, and technology education. Madrasah Ibtidaiyah combines the 2013 and independent curricula, but most teachers and parents consider Islamic learning less in-depth. Meanwhile, Madrasah Diniyah only focuses on religious teaching without including general knowledge. This research analyses the collaboration between Madrasah Ibtidaiyah (MI) and Madrasah Diniyah (Madin). The research method used is qualitative research with a case study approach. Data was obtained through observation, documentation and interviews. Data analysis refers to Miles and Huberman's theory, which involves data reduction, visualization and validation stages. The collaboration between MI Baitul Muttaqin and Madin Baitul Muttaqin involves joint decision-making to shape students' religious character and science and technology abilities through comprehensive learning between religion and science and technology. This collaboration is analyzed using collaborative governance theory, emphasizing shared goals, participation, organizational structure, role division, communication, and evaluation. The impact is comprehensive education of students' religious character and science and technology skills. The obstacles come from differences in the characteristics of Madin and MI educators, but the heads of MI and Madin consider the benefits more. Coordination, intensive communication and improving the qualifications of Madin educators are critical solutions for harmonizing learning. It is also essential to support harmonious family habits at home to achieve comprehensive results.